Socio-demographic and clinical characterization of intestinal ostomized people: an integrative literature review (Research, Society and Development, 2021)
This study aims to identify and analyze the sociodemographic and clinical characteristics of people with intestinal ostomy in the Brazilian literature. This is an Integrative Review of Scientific Literature, whose search for studies occurred in the following databases: Lilacs, CINAHL, PubMed/MedLine, BDENF, Scopus, SciELO Virtual Library and reverse search of selected articles. Of the 14 articles compiled, 78.57% have a descriptive design; the Lilacs database had the highest number of articles (64.28%); the Revista Brasileira de Coloproctologia was the one that published the most (42.85%), with a predominance of publications equally in the years 2017 and 2018 (21.42%); the Northeast region predominated in the number of articles published (49.98%). The predominant age ranged from 60 to 100 years (47.86%); married (26.64%); male (53.83%), of mixed ethnicity (20.97%), Catholic (6.51%), retired (23.11%), with elementary education (33.95%) and salary income ≤ 1 minimum wage (24.60%). There was a predominance of colostomy (83.95%), urgent (11.83%), without preoperative demarcation (4.22%), temporary permanence (42.69%), having the neoplasm as the cause main (51.14%), with complication of dermatitis (3.88%), diameter 20-40mm (1.69%), of 1 piece (16.15%), with pasty effluent (3.03%). The scarcity of Brazilian research on the subject is highlighted. However, it was possible to expand knowledge about the studied population.